2022
DOI: 10.1155/2022/3686863
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Postburn Scars following Treatment Using Dermal Substitutes

Abstract: Background. Post-burn hypertrophic scars commonly occur after burns. Studies that compare dermal substitutes with other treatment methods are insufficient. The purpose was to analyze the histopathological differences in hypertrophic burn scars after Matriderm®+split-thickness skin graft (STSG) and compare with AlloDerm®+STSG, STSG, full-thickness skin graft (FTSG), and normal skin. Methods. Samples of unburned, normal skin and deep 2nd or 3rd degree burns were obtained from patients who experienced a burn inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Elastin contents in MatriDerm® samples were almost half those of normal skin or FTG but more than SSG or Alloderm®. 37 These results and the histological findings in our current study, question the effectiveness of the elastic fibers in the MatriDerm® matrix.…”
Section: Discussionmentioning
confidence: 44%
“…Elastin contents in MatriDerm® samples were almost half those of normal skin or FTG but more than SSG or Alloderm®. 37 These results and the histological findings in our current study, question the effectiveness of the elastic fibers in the MatriDerm® matrix.…”
Section: Discussionmentioning
confidence: 44%
“…The National Burn Care, Education & Research group, The Netherlands consist of: M. E. van Baar 1,2 , L. van Dammen 1,3,4 , S. J. G. Geelen 3,5,6 , T. M. Haanstra 7-9 , D. N. Hulleman 3,5,6 , R. van Gemert 10 , C. A. Lansdorp 11 , A. Meij-de Vries 12,13 , M. K. Nieuwenhuis 5,6,14 , R. F. C. Salemans 15,16 , C. M. H. van Schie 7 , S. M. H. J. Scholten-Jaegers 3 , I. Spronk 1,7-9 , R. S. M. Thambithurai 15,17…”
Section: Funding Informationmentioning
confidence: 99%
“…Several trials have proven the effectiveness of dermal substitutes in surgical wound treatment. 3 , 4 , 5 , 6 Our recent investigation of the literature showed that a total of 25 trials have been conducted comparing the treatment outcomes of dermal substitutes with standard‐of‐care approaches (e.g., autologous split‐thickness skin) or comparing different types of dermal substitutes in patients with partial‐ and full‐thickness burns or reconstructive wounds after burns. 1 , 3 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Dermal substitutes are mainly used in acute and reconstructive burn surgery, particularly for treating deep burns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations